2015
DOI: 10.1155/2015/245953
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Macular Parameter Changes in Patients with Keratoconus Using Optical Coherence Tomography

Abstract: Keratoconus is typically diagnosed through changes at the anterior ocular surface. However, we wished to assess if macular parameter changes might also occur in these patients. We assessed posterior changes through the use of optical coherence tomography and compared to a nonkeratoconus patient group. All subjects underwent clinical examination including macular thickness measurements. The generalized estimation equation model was used to estimate the means and compare the differences in various measurements b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 28 publications
2
28
1
1
Order By: Relevance
“…The coexistence of structural retinal changes can also exist simultaneously with corneal alterations 37 ; analysis of this relationship is worthwhile, and we are in the process of performing such investigations.…”
Section: Discussionmentioning
confidence: 99%
“…The coexistence of structural retinal changes can also exist simultaneously with corneal alterations 37 ; analysis of this relationship is worthwhile, and we are in the process of performing such investigations.…”
Section: Discussionmentioning
confidence: 99%
“…1012 Interestingly, OCT of the retina has been shown to reveal small increases (~10 µm) in macular thickness in keratoconic eyes. 13 Studies have shown posterior corneal measurement by the Scheimpflug camera to dispute the theoretical properties of the posterior cornea, cautioning its use alone in diagnosing a keratoconic eye. 14, 15 The biomechanical parameters of corneal hysteresis and the corneal resistance factor have been shown to significantly decrease following LASIK surgery or with the diagnosis of keratoconus.…”
Section: Introductionmentioning
confidence: 99%
“…While many candidate genes and linkage regions have been identified in KC through previous twin/family and case-control studies, few genes have been consistently reported [1720, 31, 40–86]. Given our previous observation of posterior segment changes in the eye of KC patients [21], we sought to assess whether genes implicated in the complex eye disease of AMD may also show some involvement in KC. While the data are suggestive, given that at least 2 SNPs survive multiple correction, their involvement in this disease is not confirmed as it appears that these associations can be influenced by age and gender co-variates.…”
Section: Discussionmentioning
confidence: 99%
“…In light of the finding that genetic associations identified in one complex eye disease could also be pleiotropic with KC, we further investigated our previous observation of structural posterior segment changes in the eyes of KC patients [21]. These changes were detected by optical coherence tomography (OCT) and indicated a significantly greater mean retinal thickness in the central fovea, inner and outer macula and increased macular volume compared to non-keratoconus patients.…”
Section: Introductionmentioning
confidence: 99%